Premature Moustache As Presenting Symptom of Nonclassic Congenital Adrenal Hyperplasia due to 2 Uncommon Mutations of the CYP21A2 Gene - Guy Massa; Philippe Gillis; Marianne Schwartz (Case Reports in Genetics)
A Turkish boy was referred at the age of 3 6/12 years for the evaluation of a premature moustache. No other signs of virilisation were present. The endocrine evaluation led to the diagnosis of nonclassic congenital adrenal hyperplasia. Genetic analysis revealed 2 rare mutations of the CYP21A2 gene, the gene encoding for the 21-hydroxylase enzyme: a recently reported R132C mutation in exon 3 and a R339H mutation in exon 8, both reported in the nonclassic CAH. An early moustache, for which the term premature moustache can be coined, can be the presenting symptom of nonclassic CAH. In all children presenting with a sex or age inappropriate development of a moustache, an endocrine evaluation is indicated.